Structure and composition of trees in Mount Tilu Nature Reserve, West Java, Indonesia - Tri Cahyanto; muhammad Efendi; DIAN MUHAMAD RAMDAN (Society for Indonesian Biodiversity, 2020)
Abstract. Cahyanto T, Efendi M, Ramdan DM. 2020. Structure and composition of trees in Mount Tilu Nature Reserve, West Java, Indonesia. Biodiversitas 21: 2674-2680. An understanding of the structure and composition of stands in a conservation area is needed to support sustainable management strategy. However, this information in the Mount Tilu Nature Reserve, Bandung District, West Java area is still lacking. This research was aimed to analyze the structure and composition of tree species in the block of Malagembol forest, Mt. Tilu NR. Data collection was carried out through vegetation analysis using sampling plot method with size of 10x100 m2 at three-level altitudes of 1530 m, 1745 m, and 1950 m asl. Observation parameters included species names, number of individuals, and diameter at breast height (dbh). Data were analyzed to determine the floristic composition, species structure based on their diameter class, relative basal area, diversity indices, and analysis of the importance of the main components of trees species through Principal Component Analysis (PCA). A total of 32 tree species from 23 families was found in the observation plots which was dominated by Fagaceae, Lauraceae, and Myrtaceae families. Some pioneer plants covered the gap in vegetation due to minor disturbance and residual damage in the past. Nonetheless, the dominance of stands with small diameters indicated good regeneration status following such disturbance. Based on these findings, we recommend protecting the vegetation in Mt. Tilu NR by limiting community activities that can disturb the forest.